PENILAIAN APARTEMEN DI SURABAYA - Njo Anastasia; Samantha Christy Tandono (Universitas Trunojoyo Madura, 2014)
Focus for this apartment appraisal is the physical factor, which is involved location attribute, facilities and building of its apartment, with market comparison approach which is worked with regression. Location attribute is described into the distance between apartment and CBD area, shopping mall and hospital. Facilities attribute is divided into standard facilities and non-standard facilities which are use dummy variable. Building of the apartment is described into square meters, floor of the unit apartment, view from the apartment and number of room in the unit apartment. The result of this research is variable location; facilities and building of its apartment together determine influence of apartment market value. For facilities and view partially do not determine influence of apartment market value. The distance between apartment and CBD area, shopping mall and hospital; square meters, floor of the unit apartment and number of room in the unit apartment partially determine influence of apartment market value.